Editorial - Green, Prof S (Social Work/Maatskaplike Werk, 2019)
Thorough, topical academic research constantly generates a sound evidence base for social work teaching and learning, practice and policy development. The articles in this issue of Social Work/Maatskaplike Werk do just that. They cover a wide range of research: opportunities for HIV-infected researchers to engage in HIV-related research; authentic teaching and learning of students; effects of policies; needs of caregivers; and social problems presented by adolescents.